Visualization of Islamic Boarding School Location at Yogyakarta with Web-Based Geodesain - Alfiani, Oktavia Dewi; Wahyuningrum, Dwi; Saifullah, Shoffan; Haekal, Haekal (Telematika, 2023)
Purpose: This research produces a webGIS design that presents the geospatial location of buildings in the Krapyak Yogyakarta boarding school area to facilitate users outside the area when heading to the location of the boarding school whose buildings are scattered.Design/methodology/approach: By combining aerial photos from UAV mapping with Open Street Map. The combined results of both maps are presented in a webGIS built from HTML, CSS and OpenLayers scripting.Findings/result: Building a webGIS to present information on the location of Krapyak Islamic boarding schools that has been equipped with corrected coordinates and routes from the iconic city of Yogyakarta so that immigrants from outside the area can easily understand the use of the webgis. Originality/value/state of the art: From previous research, webGIS development only uses maps presented through openstreetmap where if users use existing online navigation applications have different coordinate system references (Soraya R, 2018). So by equalizing the map reference by combining the results of UAV mapping and correcting the shape of the building presented on openstreetmap, the spatial information from the webgis will have a position accuracy that is more in line with the truth.